Role of Stromelysin 2 (Matrix Metalloproteinase 10) as a Novel Mediator of Vascular Remodeling Underlying Pulmonary Hypertension Associated With Systemic Sclerosis. Issue 11 (17th October 2017) - Avouac, Jérôme; Guignabert, Christophe; Hoffmann‐Vold, Anna Maria; Ruiz, Barbara; Dorfmuller, Peter; Pezet, Sonia; Amar, Olivia; Tu, Ly; Van Wassenhove, Jérôme; Sadoine, Jérémy; Launay, David; Elhai, Muriel; et al.
Abstract : Objective: To elucidate the role of gene candidates involved in pulmonary hypertension (PH) associated with systemic sclerosis (SSc). Methods: Gene candidates were identified through microarray experiments performed on Affymetrix GeneChip Human Exon 1.0 ST arrays in endothelial progenitor cell (EPC)–derived endothelial cells (ECs) obtained from patients with SSc‐associated PH, patients with SSc without PH, and healthy control subjects. Expression of identified gene candidates was assessed by quantitative sandwich enzyme‐linked immunosorbent assay in the serum, and by immunohistochemistry in lesional lung tissue. The functional importance of the identified gene candidates was then evaluated in fos ‐related antigen 2–transgenic (Fra‐2–Tg) mice that spontaneously develop SSc‐like features associated with an intense pulmonary vascular remodeling. Results: Microarray experiments revealed that the matrix metalloproteinase 10 (MMP‐10) gene was the top up‐regulated gene in SSc‐associated PH EPC‐derived ECs. Circulating serum proMMP10 concentrations were markedly increased in patients with SSc‐associated PH compared to SSc patients without PH and healthy controls. Consistent with these observations, a strong MMP10 staining of the thickened wall of distal pulmonary arteries was found both in the lungs of patients with SSc‐associated PH and in the lungs of Fra‐2–Tg mice. Daily treatment of Fra‐2–Tg mice with neutralizing anti‐MMP10 antibodies did not significantly affect the development and severity of pulmonary fibrosis, but did reverse established PH and markedly reduced pulmonary vascular remodeling by reducing cell proliferation, cell survival, and the platelet‐derived growth factor signaling axis. Conclusion: Gene expression profiling of EPC‐derived ECs identified MMP10 as a novel candidate gene in SSc‐associated PH. MMP10 is overexpressed in the serum and pulmonary arteries of patients with SSc‐associated PH, and its blockade alleviates PH in the Fra‐2–Tg mouse model. MMP10 appears to be a prospective treatment target for this devastating disorder.